Time-varying contributions by the corporate bond and CDS markets to credit risk price discovery - Niko Dötz (Deutsche Bundesbank, 2007)
This paper looks at the dynamic price relationship between spreads in the corporate bond market and credit default swaps (CDS). It picks up where Blanco et al (2005) leave off but is focused on European credit markets. The study is based on companies listed in the iTraxx CDS index and thus on new data on a more liquid CDS market. Unlike previous studies, which look at price formation in a time-invariant context, the contributions of both markets to price discovery are analysed in a timevariant context. We devote particular attention to the question of whether such information input is stable in times of crisis and find that, although the CDS market slightly dominates the price discovery process, its contribution fell visibly during the turbulence on the credit markets in early 2005 in favour of that of the bond market.
Keywords: G14; G10; C32; 330; price discovery; credit risk; corporate bonds; credit derivatives; Kalman filter; Risikoprämie; Kreditrisiko; Credit Default Swap; Kreditversicherung; Industrieobligation; Zustandsraummodell; Schätzung; Zins; Europa